2012
DOI: 10.1055/s-0032-1306275
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management of Pheochromocytoma/Paraganglioma: Is There a State of the Art?

Abstract: Pheochromocytoma and paraganglioma are rare tumors of sympathetic or parasympathetic origin, presenting with a highly variable clinical picture. Rarity, as well as biological, clinical, and genetic heterogeneity are barriers to initiate prospective studies that help to establish clinical guidelines. The best management of these patients relies on the experience of a multidisciplinary team. The ultimate outcome can benefit from adequate pre-surgical evaluation and treatment as well as an accurate post-surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
(29 reference statements)
0
17
0
1
Order By: Relevance
“…Furthermore, pheochromocytomas can lead to life-threatening complications, especially in the context of medical interventions (surgery, biopsies etc.) (72,217,218). Additional hormonal work-up should depend on the stage of the extra-adrenal malignancy and life expectancy.…”
Section: Reasoningmentioning
confidence: 99%
“…Furthermore, pheochromocytomas can lead to life-threatening complications, especially in the context of medical interventions (surgery, biopsies etc.) (72,217,218). Additional hormonal work-up should depend on the stage of the extra-adrenal malignancy and life expectancy.…”
Section: Reasoningmentioning
confidence: 99%
“…Problems related to wound infection, recovery time, and image acquisition are more frequent in conventional methods as compared to laparoscopy in obese patients (8,10). In the conventional procedure; transperitoneal, retroperitoneal, lateral transperitoneal (Chevron incision), lateral (extraperitoneal), posterior (extraperitoneal), thoraco-abdominal (transpleural/ transperitoneal) approaches are being used, and it is reported that a midline incision is more appropriate for bilateral adrenalectomy (9,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Complete surgical resection with careful preoperative alpha-adrenergic blockade and subsequent beta-adrenergic blockade for any consequent tachyarrhythmia [26], in the presence of a functional pheochromocytoma, is the most appropriate therapy for CP with neuroblastoma. Prazosin is a commonly used selective alpha-1 adrenergic agonist, but requires frequent dosing due to a short half-life and its serum concentration may decrease to ineffective levels at the time of surgery if used preoperatively [27].…”
Section: Discussionmentioning
confidence: 99%